Digital Marketing Training In The "Madura" Barbershop Business In Semarang City As A Solution To Msmes' Problems In The Era Of The Marketing Revolution 5.0 - Bagus Yunianto Wibowo; Andi Setiawan; Irawan Malebra; Bayu Setyo Nugroho; Mellasanti Ayuwardani; Endang Sulistiyani; Aimi Anuar (International Journal Of Community Service, 2022)
Changes in consumer behavior due to the Covid-19 pandemic have shifted to online-based purchases. Consumers who initially made transactions directly, due to the Covid-19 pandemic, changed to make transactions online. MSMEs must quickly adapt to consumer behavior changes to survive the economic downturn. Digital marketing training is a solution to help MSMEs to adapt to changes in consumer behavior and vulnerable communities to find business and entrepreneurship opportunities through digital media. The competitiveness of the barbershop market competition demands to continue to innovate and adapt quickly. The era of destruction is a challenge for businesses that have not yet migrated to use Digital Marketing as the spearhead of expanding market reach, a new habit of modern humans who prefer a practical and easily accessible way with gadgets. MSMEs must read the opportunities and quickly keep up with the pace of the market which is controlled by digital technology. The digital market requires skills, high creativity, and consistency in creating creative content so that market interest can be taken over. Digital marketing training is already a major need for MSMEs, especially small businesses haircut "Madura" so that their existence can develop in the digital market.